Spiritual Experiences of Muslim Critical Care Nurses - Bakir, Ercan; Samancioglu, Sevgin; Kilic, Serap Parlar (Springer, 2017)
The purpose of this study was to determine the experiences and perceptions of intensive care nurses (ICNs) about spirituality and spiritual care, as well as the effective factors, and increase the sensitivity to the subject. In this study, we examined spiritual experiences, using McSherry et al. (Int J Nurs Stud 39:723-734, 2002) Spirituality and spiritual care rating scale (SSCRS), among 145 ICNs. 44.8% of the nurses stated that they received spiritual care training and 64.1% provided spiritual care to their patients. ICNs had a total score average of 57.62 +/- 12.00 in SSCRS. As a consequence, it was determined that intensive care nurses participating in the study had insufficient knowledge about spirituality and spiritual care, but only the nurses with sufficient knowledge provided the spiritual care to their patients.
Keywords: Intensive care unit; Intensive care nurses; Spirituality; Spiritual care